Identification of Rhododendron mariae extraction as a new attachment inhibitor against dengue virus by targeting the envelope protein domain III - Tian, Chunyang; Zheng, Yuanru; Tang, Dongkai; Tian, Haiyan; Shi, Lingzhu; He, Xuemei; Yu, Jianhai; Yan, Lijun; Cao, Huihui; Zhao, Wei; Liu, Junshan; Yu, Linzhong; et al. (Frontiers in Immunology, 2025)
IntroductionDengue virus (DENV), a mosquito-borne flavivirus, leads to over 390 million annual infections worldwide, and there are no approved antivirals so far. Rhododendron mariae (RM), a traditional Chinese herb abundant in flavonoids and triterpenoids, is used to treat respiratory disorders, yet its antiviral potential has been little explored. This study sought to assess the activity and mechanism of RM-1, an extract from RM, against DENV.MethodsIn vitro, plaque reduction assays in BHK-21 cells were used to determine RM-1’s half-maximal effective concentration (EC50) against DENV-2. Its broad-spectrum activity against the four DENV serotypes was tested in Vero and Huh7 cells. In vivo, DENV-infected suckling mice were given RM-1 (10 mg/kg), with monitoring of viral loads, histology, and survival. Mechanistic studies included attachment assays and molecular docking to find potential targets.ResultsRM-1 strongly inhibited DENV-2 (EC50=2.24 μg/mL) and showed dose-dependent activity against all four serotypes by blocking viral attachment. In infected mice, RM-1 lessened disease severity, reduced tissue lesions, lowered viral loads in serum, brain and spleen, and boosted survival rates. It targeted DENV envelope protein domain III (ED III), which is critical for host attachment.DiscussionThis is the first report that RM-1 acts as a novel DENV attachment inhibitor by targeting ED III. These findings show RM-1’s promise as an anti-dengue therapeutic, supporting traditional herbs as sources of antivirals for flavivirus drug development.